Overexpression of αCGRP promotes osteogenesis of periodontal ligament cells by regulation of YAP signaling. Issue 4 (6th September 2018) - Xiang, Lin; Zhang, Xinyuan; Yu, Hui; Wang, Bin; Lin, Zhihui; Gong, Ping
Abstract: Human periodontal ligament cells (hPDLCs) are considered as an ideal cell type for periodontal tissue engineering as hPDLCs own mesenchymal stem cell‐like properties. Additionally, it is suggested that α‐calcitonin gene‐related peptide (αCGRP) plays a pivotal role in the pathogenesis of periodontitis. However, the specific role of αCGRP on the regulation of alveolar bone regeneration which is essential for treatment of periodontitis remains unclear. In this study, lentiviral αCGRP expression vector was first transfected into hPDLCs. αCGRP expression and the osteogenesis‐related gene (ALP, RUNX2, OCN, and BSP) expressions were detected. The results showed that expressions of osteogenic phenotypes were upregulated in αCGRP‐transfected hPDLCs combined with an increased expression of Yes‐associated protein (YAP), which is the key downstream effectors of Hippo pathway. Our observations suggest that αCGRP‐mediated hPDLCs' osteogenesis might relate with the activity of YAP signaling. These observations may reflect intrinsic functions of αCGRP in hPDLCs' osteogenesis and its promising role in the treatment of bone deficiency in periodontal regeneration. Abstract : Our findings suggest that human periodontal ligament cells (hPDLCs) transfected with α‐calcitonin gene‐related peptide (αCGRP) lentiviral vector system maintain their basic biological characteristics and provide a safe profile with robust and sustained transgene expression. αCGRP promotes the differentiation of hPDLCs into mineralized tissue‐forming cells which is related with its downstream branch Yes‐associated protein signaling. In all, it is expected that hPDLCs transfected with αCGRP might serve as an appropriate therapy for the safe and predictable restoration of alveolar bone loss caused by periodontitis